A SIMPLE AND EFFICIENT METHOD FOR DNA EXTRACTION FROM RABI SORGHUM [Sorghum bicolor (L.) MOENCH] - S. S. GADAKH; G. D. KHALEKAR; U. S. DALVI; A. A.KALE; P.L.KULWAL (The Bioscan, 2020)
Sorghum [Sorghum bicolor (L.) Moench] is an important source for bio-energy and having significant contributions in agriculture. Accordingly, plant breeders are working for different strategies for genetic improvement i.e. breeding for higher yield, improved grain quality, and biotic and abiotic stress tolerance in sorghum. For genetic improvement four major biotechnological tools are now emerging e.g. molecular markers, gene identification and cloning, genetic engineering and gene transfer technology to integrate desirable traits into the sorghum genome, and genomics and germplasm databases. Genomic DNA extraction is the basic prerequisite for all of these tools. We made several modifications to the available CTAB method to isolate genomic DNA from sweet sorghum leaf tissues. Higher concentration of NaCl (5 M) in CTAB extraction buffer improved the DNA yield and quality by preventing the sample from becoming viscous during the sample grinding. The yield of DNA ranged from 432-569 ng from 200 mg of leaf tissue. Proteinase k and RNase A treatment properly removes the protein and RNA from DNA. An absorbance value of 1.8 at A260/A280 indicates that the DNA is free from RNA and protein contamination. Three times chloroform:isoamyl alcohol (24:1 v/v) wash resulted in a good quality of DNA. Pre-chilled ethanol being useful for DNA precipitation due to its volatile nature and ideal for small and medium scale DNA extraction. PCR analysis using SSR primers shows a consistent and reliable amplification